198Prevalence of illicit substances in personal vaporisers on online cryptomarkets. (2nd September 2021) - Lim, Miss Carmen; Leung, Janni; Connor, Jason; Hall, Wayne; Cheng, Brandon; Gartner, Coral; Scheurer, Roman; Chan, Gary
Abstract: Background: Personal vaporisers or e-cigarettes are gaining popularity as an alternative route of administration for illicit substances. Data from the Centers for Disease Control and Prevention on the recent epidemic of vaping related lung injuries has confirmed that victims had vaped blackmarket tetrahydracannabidiol, including some sourced from online cryptomarkets. We examined the diversity and prevalence of illicit substances in vaping products available from these marketplaces. Methods: Vaping related listings were extracted from three online cryptomarkets ('Agartha', 'Cryptonia', and 'Tochka') using The Onion Router browser. Data collection occurred between October and November 2019. Results: We identified 1929 listings from 201 unique sellers. The top product across the three markets were vape cartridges (range = 39.4% to 70.4%). The most common substance in these products was cannabis oil (range = 82.1% to 96.1%), followed by synthetic cannabinoids (range = 3.7% to 9.8%) and psychedelic substances (range = 0.2% to 6.4%). Vendors were primarily from the USA. Many products offered worldwide shipping (range = 42.4% to 96.3%). Conclusions: Our study fills knowledge gaps by providing information on what vaping products are being sold through online cryptomarkets. Future studies should continue to monitor cryptomarkets to identify emerging trends of substances used in personal vaporisers. Key messages: Online cryptomarkets provide a new way of monitoring emerging vaping trends and identify factors that contributes to the current vaping epidemic.